Impedance modeling for a unit cell of the square loop frequency selective surface at 2.4 GHz - Mohamad Zoinol Abidin, Abd. Aziz (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Link to publisher's homepage at http://ieeexplore.ieee.org/